2019
DOI: 10.1002/ejoc.201901381
|View full text |Cite
|
Sign up to set email alerts
|

Decarboxylative C–C and C–N Bond Formation by Ligand‐Accelerated Iron Photocatalysis

Abstract: The photoexcited state lifetimes of iron complexes are typically much shorter than those of iridium and ruthenium complexes. For that reason, iron complexes find less application in photochemical organic synthesis. Through iron photocatalysis, a mild and effective protocol for decarboxylative C-C and [a]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(72 citation statements)
references
References 39 publications
1
68
0
3
Order By: Relevance
“…Jin's group has described the use of photoexcited Fe-catalyzed decarboxylative coupling to form C-N bonds in hydrazines (Scheme 76). 48 Mechanistically (Scheme 77), this visible-light-excited redox-neutral process was believed to be similar to the C(sp 3 )-C(sp 3 ) coupling developed by the same group (see Scheme 74). 48 Scheme 76 Photoexcited Fe-catalyzed decarboxylative coupling to form hydrazines H. Chen et al…”
Section: Fe-catalyzed Decarboxylative C-n Bond Formationmentioning
confidence: 84%
See 1 more Smart Citation
“…Jin's group has described the use of photoexcited Fe-catalyzed decarboxylative coupling to form C-N bonds in hydrazines (Scheme 76). 48 Mechanistically (Scheme 77), this visible-light-excited redox-neutral process was believed to be similar to the C(sp 3 )-C(sp 3 ) coupling developed by the same group (see Scheme 74). 48 Scheme 76 Photoexcited Fe-catalyzed decarboxylative coupling to form hydrazines H. Chen et al…”
Section: Fe-catalyzed Decarboxylative C-n Bond Formationmentioning
confidence: 84%
“…Under visible-light irradiation, carboxylic acids underwent a radical decarboxylative reaction with 2-arylidenemalononitrile in the presence of an Fe catalyst (Scheme 73). 48 Different from the oxidative C(sp 3 )-C(sp 2 ) couplings (see Scheme 65), 45 this protocol was redox-neutral in which the oxidation of Fe II back to Fe III was realized by the electron-deficient radical intermediates (Scheme 74): Fe III 74.1 coordinates with carboxylic acid 74.2 to form Fe III -carboxylate complex 74.3, which is photoexcited and undergoes an intramolecular charge-transfer event to generate Fe II 74.4 and carboxyl radical 74.5. This radical releases CO 2 to become alkyl radical 74.6.…”
Section: Review Synthesismentioning
confidence: 99%
“…With continuous interest in such iron photocatalysis, Jin and co‐workers further achieved a redox‐neutral process with high decarboxylation efficiency by ligand modulation, which enabled the C−C and C−N bond formation (Scheme 12 b). [26a] In both cases (Scheme 12 a and b), the reaction was inhibited by the addition of a free radical scavenger, indicating the involvement of radical intermediates. The light/dark experiments demonstrated that the constant irradiation of visible light was necessary to drive the alkylation to completion.…”
Section: Light‐induced Iron Photoredox Catalysismentioning
confidence: 96%
“…Jin's group has developed an alternative protocol for the decarboxylative C-N coupling reaction using an iron catalyst prepared in situ by complexation of Fe 2 (SO 4 ) 3 with a di-(2-picolyl)amine ligand (Scheme 52). 56 Azodicarboxylates and carboxylic acids were successfully coupled to give aliphatic amines. The oxidation of Fe(II) back to Fe(III) by the electron-deficient radical intermediates is proposed to be the key process for the redox-neutral coupling reaction.…”
Section: Scheme 51 Aminodecarboxylation Of Carboxylic Acidsmentioning
confidence: 99%